Correction: Relationship between weight and linear dimensions of Bluefin tuna (Thunnus thynnus) following fattening on western Mediterranean farms. - Vicente Puig-Pons (Public Library of Science (PLoS), 2021)
[This corrects the article DOI: 10.1371/journal.pone.0200406.].